Frase Nomina Bahasa Gorontalo - Usman, Alfian (Kajian Linguistik, 2015)
The objectives of the study are toidentify the form of Â noun phrase inGorontalo language and to analyze the normaland abnormal mapping of noun phrasein Gorontalo language by using tagmemic analysis. The results of the study showthat (1) noun phrases in Gorontalo language consist of (a) N = +Det +H:n; (b) N= +H:n +Mod:n; (c) N = +H:n +Mod:adj; (d) N = +H:n +Mod:v;(4) N = +H:n +Mod:adv; (e) N = +H:n +Qn:qn; (f) N = +H:n +Det:det;(g) Nco = +H1:N/n +C:c (wau) +H2:N/n and Nco= +H1:N +C:c (woli/wole/wolilei/wolemei) +H2:n; (h) N =+H:n +Mod:RA; (i) N = +H:n +Id:rel.Cl; (2) In normal mapping nounphrase fills the subject, object, and complement slot. Abnormal mapping consistsof layering, back-looping and level skipping. In layering, noun phrase filledby noun phrase, adjectival phrase, numeral phrase and relator axis phrase(locational and temporal) as direct element; in back-looping noun phrase isfilled by relative clause as direct element; in level skipping noun phrase isfilled by bound morpheme (possesive marker) as direct element.Keywords:Noun Phrase, Gorontalo Language, Tagmemic Analysis